An upconversion nanoparticle-integrated fibrillar scaffold combined with a NIR-optogenetic strategy to regulate neural cell performance. Issue 2 (16th December 2022) - Wu, Chengheng; Su, Borui; Xin, Nini; Tang, Jiajia; Xiao, Jiamei; Luo, Hongrong; Wei, Dan; Luo, Fang; Sun, Jing; Fan, Hongsong
Abstract : By integrating upconversion nanoparticles (UCNPs) with a bioactive scaffold with an oriented fibrillar structure, the NIR-responsive neuro-matrix interface is generated to activate light-sensitive protein CatCh for optogenetic neurogenesis regulation. Abstract : Optogenetics using light-sensitive proteins such as calcium transport channel rhodopsin (CatCh) opens up new possibilities for non-invasive remote manipulation of neural function. However, current optogenetic approaches for neurological disorder therapies rely on visible light excitation and are rarely applied to neurogenesis and nerve regeneration. Herein, we propose a new strategy for tissue engineering which combines optogenetic technology and biomimetic nerve scaffolds. Upconversion nanoparticles (UCNPs) were synthesized and integrated with oriented fibrillar PCL membranes with a collagen coating to establish neuro-matrix interfaces. Benefiting from the excellent bioactivity, oriented fibrillation and NIR-photoresponsivity, the CatCh-transfected PC12 cells on these interfaces exhibited enhanced cell elongation and neurite extension, as well as upregulated neurogenesis upon NIR excitation. Furthermore, a UCNP-integrated scaffold as an optogenetic actuator allowed NIR to penetrate dermal tissues to mediate neural activation, with an efficiency comparable to that of a 470 nm blue light. Compared with current visible light-excited optogenetics, our composite scaffold-mediated NIR stimulation addresses the problem of tissue penetration and will enable less-invasive neurofunctional manipulation, with the potential for remote therapy.